Professional Competence Development in Practicum: A Holistic Teacher Profile Construction - García Chamorro , Martha C.; Rolong Gamboa, Monica Tatiana (Colombian Applied Linguistics Journal, 2025)
Practicum in language teacher education is a fundamental component of teachers’ preparation because in this practice, results associated with pedagogical competencies are normally expected. However, these competences are also the result of other processes that influence and include the teacher in a context in which challenges emerge. This study analysed from what dimensions the experience of these practices helps to develop the effectiveness of teachers in terms of knowledge, skills and attitudes within a framework of formative and reflective research. For this descriptive qualitative research, from a case study of three pre-service teachers and their tutor during two-and-a-half years, semi-open interviews, their research tutor’s mentoring document, and artifacts created in the in the practicum span were used. The results show that the pedagogical practices offered opportunities taking into account the dimensions of context, quality of experience, personal construction and knowledge acquired at their program to develop knowledge, skills and attitudes with a view to give meaning and sense to theory and practice within a learning environment as long as it is framed in support and reflective guidance in mentoring.